The impact of social participation on Subjective Wellbeing in the older adult: the mediating role of anxiety and the moderating role of education - Qing, Zaihua; Wu, Caihong; Gao, Tao (Frontiers in Public Health, 2024)
Introduction The study aims to examine the mediating role of anxiety in the relationship between social participation and Subjective Wellbeing among Chinese older adults. Additionally, it investigates the moderating ed of education in this relationship. Methods The data came from the Chinese Longitudinal Healthy Longevity Survey (CLHLS) published by peking University, with a sample size of 10,626 individuals aged 60 years and above. SPSS 21.0 was used for the statistical analysis of the data, and Mplus 8.0 was used for the statistical processing of the mediating and moderating effects analysis. Results (1) The social participation significantly and positively predicated Subjective Wellbeing; (2) Anxiety partially mediated the eect between social participation and Subjective Wellbeing. The mediating eect value was 0.103; (3) Education plays a moderating role in the impact of social participation on subjective Wellbeing. Discussion In summary, social participation can reduce the anxiety and enhance their Subjective Wellbeing. Meanwhile, the eet of social participation on Subjective Wellbeing was the greatest for the older adult with high education. The findings suggest that community-led activities can be initiated to improve social participation in the older adult. Furthermore, educational courses could be to support the healthy aging of older adults in China.